Long distance commuting in Chile: estimating the prize for working far away from home - Jamett Sasonov, Iván; Paredes Araya, Dusan (Estudios de Economía, 2013)
The importance of Long Distance Commuting (LDC) has increased as a result of the continuous reduction of transport costs. This paper formalizes the relationship between LDC and wage through a job search model where a commuting time variable is included. The paper proposes that LDC be compensated in wage and be increasing in distance, and that the regions which receive more commuters pay a higher premium wage. The results suggest an average premium of 19% for LDC. However, the applicable rate depends on the workplace location of each commuter, and thus it might be as high as 40%.